Handel zagraniczny czy bezpośrednie inwestycje zagraniczne? Przykład krajów Europy Środkowej i Wschodniej - Klimek, Artur (Foreign Trade or Foreign Direct Investments. Evidence from CEE Countries, 2008)
The main goal of the paper is to examine the effect of FDI on trade of CEE countries. The author investigates if the foreign production and trade are substitutes or complementaries for the selected group of countries. Most previous empirical studies were devoted to highly developed countries and this is one of the first attempts to test this relationship in CEE. The results of the finding will also help answer the question about the changes in internationalization process of the CEE firms and relation between exports and outward FDI as a way of servicing foreign markets.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 99-108